2016
DOI: 10.1186/s12974-016-0720-6
|View full text |Cite
|
Sign up to set email alerts
|

MOG-IgG in NMO and related disorders: a multicenter study of 50 patients. Part 4: Afferent visual system damage after optic neuritis in MOG-IgG-seropositive versus AQP4-IgG-seropositive patients

Abstract: BackgroundAntibodies against myelin oligodendrocyte glycoprotein (MOG-IgG) have been reported in patients with aquaporin-4 antibody (AQP4-IgG)-negative neuromyelitis optica spectrum disorders (NMOSD). The objective of this study was to describe optic neuritis (ON)-induced neuro-axonal damage in the retina of MOG-IgG-positive patients in comparison with AQP4-IgG-positive NMOSD patients.MethodsAfferent visual system damage following ON was bilaterally assessed in 16 MOG-IgG-positive patients with a history of ON… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
195
1
13

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 223 publications
(228 citation statements)
references
References 41 publications
19
195
1
13
Order By: Relevance
“…However, previous reports indicated that most of the MOG-Ab-positive patients presented as monophasic disease or had less relapsing rate,8 9 which was different from the current study demonstrating both patients with MOG-ON and AQP4-ON had high recurrent episodes. However, in some other studies, patients with MOG-ON were frequently associated with a recurrent disease course 14. This study indicated that Chinese patients with MOG-ON might also have a high tendency to relapse, so that long-term immunotherapy should be considered in relapsing patients with MOG-ON.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…However, previous reports indicated that most of the MOG-Ab-positive patients presented as monophasic disease or had less relapsing rate,8 9 which was different from the current study demonstrating both patients with MOG-ON and AQP4-ON had high recurrent episodes. However, in some other studies, patients with MOG-ON were frequently associated with a recurrent disease course 14. This study indicated that Chinese patients with MOG-ON might also have a high tendency to relapse, so that long-term immunotherapy should be considered in relapsing patients with MOG-ON.…”
Section: Discussionmentioning
confidence: 64%
“…In our previous study, the BCVA in AQP4-Ab-negative ON eyes was better than AQP4-Ab-positive ON eyes 28. In NEMOS of Caucasian descent,14 the patients’ VA was less impaired in the MOG-ON subgroup than in the AQP4-ON subgroup after more than 3 months follow-up, but the difference was not significant. The results from our Chinese cohort showed that the onset episode severity of patients with MOG-ON was similar to AQP4-ON ones but had a better visual recovery for the former group of patients.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In addition, no patients were seropositive for anti‐aquaporin‐4 antibodies, but both studies identified antibodies to myelin oligodendrocyte glycoprotein (MOG) in one patient with recurrent/bilateral ON (RON/BON) (Soelberg et al., 2017). The presence of anti‐MOG antibodies in patients with RON/BON is also in accordance with other studies (Chalmoukou et al., 2015; Pache et al., 2016). …”
Section: Discussionmentioning
confidence: 99%
“…The discovery and investigation of aquaporin-4 (AQP4)-antibodies [21,[31][32][33][34][35] have revolutionized NMOSD diagnostics by setting the disease apart from MS [36,37] and substantially changing NMOSD treatment [38] which considerably differs from classic diseasemodifying treatment in MS [39][40][41][42][43][44][45][46][47][48]. However, especially against the background of emerging evidence on myelin oligodendrocyte glycoprotein (MOG) -antibody-positive cases related to NMOSD, the heterogeneous pathophysiology of NMOSD still needs to be fully elucidated [49][50][51][52][53][54][55][56][57][58].…”
Section: Nmosd Visual Pathway White Matter Damage Patternsmentioning
confidence: 99%